A Conceptual Study of Viruddhahar (food incompatibilities) with special reference to Current Food Articles & Dietary Habits - Khuje, Sanjeev; Singh, Archana (International Research Journal of Ayurveda & Yoga, 2024)
Viruddhahar i.e. Incompatible or antagonistic food is one of the important concepts of Ayurvedik science and it is believed that consumption of incompatible foods (foods holding opposite properties) may lead various pathological manifestations. Variety of food incompatibilities are mentioned in Ayurvedic literature, which are not in practice now a days. But there are various new food incompatibilities, which are practiced currently in day-to-day life and produces harmful effects such as deterioration of immune system, cellular metabolism, growth hormone etc. Understanding of these food incompatibilities and there harmful effects is need of hour now. In this paper we are reviewing the concept of Viruddhahar and effort has been made to understand the incompatibility of current food articles and dietary habits with special reference to Viruddhahar.